2020 25th International Conference on Pattern Recognition (ICPR) 2021
DOI: 10.1109/icpr48806.2021.9412392
|View full text |Cite
|
Sign up to set email alerts
|

Watch Your Strokes: Improving Handwritten Text Recognition with Deformable Convolutions

Abstract: Handwritten Text Recognition (HTR) in free-layout pages is a valuable yet challenging task which aims to automatically understand handwritten texts. State-of-the-art approaches in this field usually encode input images with Convolutional Neural Networks, whose kernels are typically defined on a fixed grid and focus on all input pixels independently. However, this is in contrast with the sparse nature of handwritten pages, in which only pixels representing the ink of the writing are useful for the recognition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…This evolution in technology highlights a deep understanding of model adaptability and non-local structural modeling capabilities, providing robust support for research and applications in the field of computer vision. Iulian Cojocaru et al [40] introduced deformable convolution into handwritten text recognition, recognizing that standard convolutional operators do not explicitly consider the significant variability in the shape, proportion, and orientation of handwritten characters. To overcome these limitations, the authors studied deformable convolution and ultimately demonstrated its effectiveness in handwritten recognition.…”
Section: Deformable Convolutionmentioning
confidence: 99%
“…This evolution in technology highlights a deep understanding of model adaptability and non-local structural modeling capabilities, providing robust support for research and applications in the field of computer vision. Iulian Cojocaru et al [40] introduced deformable convolution into handwritten text recognition, recognizing that standard convolutional operators do not explicitly consider the significant variability in the shape, proportion, and orientation of handwritten characters. To overcome these limitations, the authors studied deformable convolution and ultimately demonstrated its effectiveness in handwritten recognition.…”
Section: Deformable Convolutionmentioning
confidence: 99%
“…This strategy was the standard one [6,19,35] until simpler alternatives to MDLSTM-RNNs were proposed [38,43]. These consist of a ConvNet to extract a sequence of feature vectors from the text image and 1D-LSTMs to output character probabilities for the CTC decoding and became commonly used as a backbone for HTR systems [8,13,16,36,50] due to its performance and faster training compared to MDLSTMs.…”
Section: Related Workmentioning
confidence: 99%
“…As a consequence, deformable convolutions can adapt to the input geometric variations and part deformations, making them potentially more suitable for dealing with HTR images compared to standard convolutions. This kind of convolution has been originally proposed to tackle the object recognition task and, to the best of our knowledge, its usage in HTR has been explored only in our preliminary work [16], where we claim that its kernel adaptability (see Figure 1) can help to improve the efficiency and the performance in the task. In this work, we deepen our analysis and extend it to HTR on historical manuscripts.…”
Section: Introductionmentioning
confidence: 99%